Spatial and temporal monitoring of surface water area changes in Abhe Lake during 2017-2022 using satellite images and GIS (مجلة الفاروق للعلوم, 2026)
Lake Abhe, also called Lake Abbe, is one of six connected lakes that lies on the Ethiopia-Djibouti border. This lake is considered the ultimate destination of the Awash River in the center of the Afar Triangle. It occupies a significant portion of the water resources in the region. The current surface water area of the lake is 347.00 sq.km by the end of this study; however, the surface water area has changed significantly since 1900. Therefore, this study focuses mainly on the continuous monitoring of the surface water changes from 2017 to 2022 using satellite images and Geographic Information Systems (GIS). Operational land images (OLI) Landsat 8 images were processed to estimate the surface water area using a GIS slice tool in ArcGIS to distinguish the water body from the dry land. Some obvious changes have been observed, with significant transformation showing a shrinking trend from the beginning of 2017 to July 2020, followed by an expansion trend from August 2020 to the end of 2022. By comparing the results of this investigation with climate data, it can be concluded that these investigations indicate that the fluctuations in the surface water area in Abhe Lake have been caused by climate changes, specifically the precipitation rate. Overall, these changes should be monitored to ensure the sustainability of water in the lake region.